Counseling on Transportation Logistics Curriculum Level III Jabodetabek Region - Haholongan, Rutinaias; Sakti, Sri Handoko; Syamsuar, Ginanjar; Pratama, Bayu; Husen, Irfan Arif (Entrepreneurship and Community Development, 2023)
Logistics transportation manages and provides transportation facilities and infrastructure for smooth logistics distribution. Logistics activities or freight forwarding services refer to the management and distribution of logistics goods obtained from users, stored in logistics warehouses, sorted shipments, and transported and sent to the destination address. Logistics activities have an important role in a business company, but the important role of logistics transportation is also major in distributing goods. This activity aims to produce graduates of experts who are reliable and best in transportation and logistics and have a reputation for ready-to-use labor. The methods used are lectures, discussions, and questions and answers. The implementation of the training activities of the participants was no obstacle in conducting counseling, and the internet connection was not interrupted. In support of infrastructure, facilities are adequate, namely the availability of laptops or personal computers from participants so that all participants can take part in counseling optimally